EFIKASI DIRI DAN DUKUNGAN SOSIAL KELUARGA DENGAN EMOTIONAL FOCUSED COPING INDIVIDU TUNARUNGU KOMUNITAS AREK TULI - Mutiara Oktaviani Abdullah; Puri Aquarisnawati; Ahmad Burhan Wijaya (Fakultas Psikologi Universitas Hang Tuah, 2022)
This study aims to determine the relationship between self-efficacy and emotional focused coping, the relationship between family social support and emotional focused coping, and the relationship between self-efficacy and family social support with emotional focused coping in deaf individuals in the Arek Tuli Community in Surabaya-Sidoarjo. This study uses a quantitative approach. The number of research subjects as many as 42 deaf. The sampling technique used incidental sampling. Study result found that there is no positive relationship between self-efficacy and emotional focused coping, there is no positive relationship between family social support and emotional focused coping, there is no positive relationship between self-efficacy and family support with emotional focused coping in deaf individuals in the Arek Tuli Community in Surabaya-Sidoarjo.This happens because there are other factors more related to emotional focused coping such as age and type of problem.